(In)Effectiveness of In-Home Detention Tethers to Reduce Recidivism for System-Involved Girls. (9th May 2022) - Anderson, Valerie R.; Rubino, Laura L.; McKenna, Nicole C.; Campbell, Christina A.; Petkus, Amber A.; Barnes-Lee, Ashlee R.
Abstract: In-home detention tethers are an intermediate, correctional sanction that have become popular alternatives to detention or incarceration. However, there is limited research on whether in-home detention tethers reduce recidivism among juvenile legal system involved girls. The current quasi-experimental study examines recidivism outcomes among adjudicated girls who received the intervention compared to a matched comparison group of girls. Recidivism rates were analyzed following completion of the intervention. In-home detention tethers were not found to be an effective method to reduce recidivism among girls.